Micro, Small and Medium Enterprises (MSMEs) Strategy in Maintaining Business Amidst the COVID-19 Pandemic (Case Study in Gampong Pasar, Tapaktuan District, South Aceh Regency) - Husnilasari, Riza; Mardiaton, Mardiaton (International Journal of Economics Studies, 2025)
This research is motivated by the impact of the Covid-19 pandemic which has spread widely on the development of Micro, Small and Medium Enterprises (MSMEs). MSME income has decreased and some have been forced to close their businesses due to the Covid-19 Pandemic. In this case, MSMEs must find the right strategy to survive. The strategies that can be carried out during the pandemic are Product Strategy, Price Strategy, Promotion Strategy, Place/Distribution Strategy, Online Marketing Strategy (e-marketing). This study aims to determine what types of businesses are affected by the Covid-19 pandemic and determine the right strategy to maintain their businesses for MSMEs. This study uses a qualitative method through case studies, which produces descriptive data. The data sources in this study use Primary and secondary data using the Purposive Sampling technique. In this study, researchers visited several MSMEs located in Gampong Pasar, Tapaktuan District, South Aceh to conduct interviews and direct observations with informants.